Predicting Acetabular Component Size in Bipolar Hip Hemiarthroplasty Using Digital Radiographs: A Prospective Study on Accuracy - Umesh Samria; Naveen Sathiyaseelan; Akib Nisar Sheikh; Pankaj Jain; Pradeep Khinchi (Journal of Clinical and Diagnostic Research)
Introduction: Elderly individuals frequently suffer from hip fractures, particularly femoral neck intracapsular fractures, which can cause serious morbidity. Bipolar hip hemiarthroplasty is a preferred treatment for displaced fractures, but accurate preoperative templating is essential to predict acetabular component size and to improve surgical outcomes. Aim: To assess the accuracy of preoperative digital radiographs in predicting acetabular component size for bipolar hip hemiarthroplasty, thereby improving surgical planning and implant selection. Materials and Methods: A hospital-based prospective study was conducted at SMS Hospital, Jaipur, Rajasthan, India, involving 50 patients undergoing bipolar hip hemiarthroplasty from November 2017 to December 2019. The primary inclusion criteria included age over 20, a diagnosis of hip arthrosis or femoral neck fracture, skeletal maturity, no significant concomitant disorders, and informed consent to participate. The demographic parameters included age, gender, Body Mass Index (BMI), diagnosis (hip arthrosis or femoral neck fracture according to Garden's classification), side of hip involvement, and ethnicity/race (if applicable) for anatomical variations. Preoperative digital radiographs were analysed using templating software to predict the acetabular component size. Intraoperatively, the actual implant size was determined and compared with the predicted size. Accuracy, deviations, and influencing factors were assessed using statistical analysis. A paired t-test was used to compare the predicted acetabular component sizes with the actual intraoperative sizes and to evaluate the reliability of digital radiographs for preoperative sizing. A p-value of < 0.05 was considered statistically significant for all tests. Results: The predicted acetabular size ranged between 40 and 53 mm, with an accuracy of 14 (28%) for the exact size and 42 (84%) within one size including the most accurate ones. Accuracy was slightly higher in female patients at 24 (90%) compared to males at 18 (78.3%). The inconsistencies were attributed to the limited availability of prosthesis sizes and the quality of radiography. Conclusion: Digital templating improves preoperative planning for bipolar hip hemiarthroplasty, but it is less accurate than for Total Hip Arthroplasty (THA). To improve the templating outcomes in clinical practice, it is advised to implement better radiography techniques, calibration protocols, and surgeon training.